AB0110 Iguratimod inhibits rankl-induced osteoclastogenesis in raw264.7 cells. (23rd January 2014) - Tan, W.; Gan, K.; Zhang, M.; Feng, X.; Wang, F.
Abstract : Background: Iguratimod, also named as T- 614, is a member of the family of methanesulfonanilide. We previously reported that Iguratimod is effective and well tolerated for treatment of patients with active RA in a multicenter, randomized, double-blind, controlled trial, which make it develop as a novel disease-modifying antirheumatic drug for RA in China and Japan. Many efforts have been made recently to explore the mechanism of Iguratimod for treatment RA. Growing evidences indicated that Iguratimod could reduce the production of various inflammatory cytokines, including interleukin-1β (IL-1β), IL-6, IL-8, IL-17, tumor necrosis factor α, and interferon-γ and stimulate osteoblastic differentiation in vitro and in vivo. However, whether iguratimod could affect osteoclastogenesis remain unknown. Objectives: To study the effect of iguratimod on osteoclastogenesis in osteoclast precursors RAW264.7 cell line. Methods: Osteoclast differentiation was induced by the receptor activator for nuclear factor κB ligand (RANKL) in RAW264.7 cells in the presence or absence of Iguratimod. Osteoclast formation was evaluated tartrate-resistant acid phosphatase (TRAP) staining. Gene expressions of osteoclastic marker was analyzed by Real time quantitative PCR. The expressions of NFATc1, c-Jun and c-Fos protein and phosphorylation of NF- κ B p50 and JNK signaling pathway in RAW264.7 cells were examined by western-blot. Bone resorption activity of mature osteoclast was tested by pit formation assay. Results: Iguratimod strongly inhibited osteoclast differentiation in a dose-dependent manner. RANKL-induced expression of NFATc1, c-Jun, c-Fos, metalloproteinase-9 and cathepsin K were suppressed by Iguratimod in the RAW264.7 cells. Furthermore, Iguratimod could downregulate phosphorylation of the NF- κB p50 and JNK signaling pathway and inhibited the bone-resorbing activity of mature osteoclasts measured by osteologic discs. Conclusions: These results indicate that iguratimod is a potent inhibitor of osteoclastogenesis, supporting its therapeutic benefit for preventing bone erosion in RA. References: Lu LJ, Bao CD, Dai M, Teng JL, et al. Multicenter, randomized, double-blind, controlled trial of treatment of active rheumatoid arthritis with T-614 compared with methotrexate. Arthritis Rheum. 2009 Jul 15;61(7):979-87. Disclosure of Interest: None Declared